Analisis Kemampuan Problem Solving Ditinjau dari Representasi Matematis Pada Materi SPLDV - Nabila, Dyah Seftiah; Syutaridho, Syutaridho (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA, 2024)
This research aims to describe the presentation of problem solving ability incidents in terms of mathematical representation in System of Linear Equations in Two Variables (SPLDV). Problem solving is a learning process that uses students' problem solving abilities with certain stages. Representation is a model or alternative form of a problem situation that is used to find a solution. For example, a problem can be represented using objects, images, words, or mathematical symbols. This type of research is a descriptive qualitative type. The subjects in this research are class VIII students at MTs Darul Huda, Air Kumbang District 7 people, with the subject taking technique using purposive sampling technique. The research instrument used was LKPD with a problem solving approach to SPLDV material. Data collection was carried out by means of interviews and student test results , and draw conclusions.. The results of the research show that students who master 3 mathematical representations are able to solve a problem based on the problem solving stages compiled by Polya. Although there are students who have problems solving problems and have problems re-checking the answers they get